Endocrinology of aging males - Rabijewski, Michał; Zgliczyński, Wojciech (Menopause Review/Przegląd Menopauzalny, 2010)
Aging in men is accompanied by gradual decline of all physiological functions, involving the heart, lungs, kidneys, liver and brain as well as the endocrine systems. The symptomatology is characterized by a decrease in general well-being, work capacity, muscle mass and strength, virility, sexual pilosity, libido and sexual activity, by a greatly increased frequency of impotence, increased body fat, osteopenia and atherosclerosis, and a decline in cognitive performance, forgetfulness and sleep disturbances. Many of these symptoms are reminiscent of symptoms of hormone deficiency such as hypogonadism, growth hormone (GH), deficiency or hypothyroidism, although it often remains difficult to evaluate the relative contribution of the aging process itself, the endocrine alterations or the permanent consequences of previous diseases to the symptomatology in aging males. We present here some reflections on the involvement of the endocrine system in the aging process in men.